Analysis of pregnancy-associated factors after fertility-sparing therapy in young women with early stage endometrial cancer or atypical endometrial hyperplasia - Yuan Fan; Xingchen Li; Jiaqi Wang; Yiqin Wang; Li Tian; Jianliu Wang (BMC, 2021)
Abstract Background Fertility-sparing therapy is an alternative conservative treatment for patients with early stage endometrioid cancer or atypical endometrial hyperplasia. In this study, we investigated pregnancy outcomes and pregnancy-associated factors in young patients receiving hormonal therapy. Methods We retrospectively analyzed 68 patients who attempted to conceive after fertility-sparing therapy and achieving complete remission (CR). They were divided into a pregnancy group and a non-pregnancy group. A Cox proportional hazard regression model was applied for univariate and multivariate analysis to determine factors associated with pregnancy. Kaplan-Meier analysis, combined with the log-rank test, was used to calculate a patient's pregnancy probability and the distribution of recurrence-free survival (RFS). Results A total of 36 patients became pregnant with 47 pregnancies. Univariate and multivariate Cox analysis revealed that several factors were associated with pregnancy, including BMI at the time of pregnancy permission, the time to CR, prolonged treatment time, the number of hysteroscopy procedures, the endometrium thickness after CR, and relapse before pregnancy. The mean RFS of patients who achieved pregnancy, and those who did not, was 27.6 months and 14.8 months, respectively (P = 0.002). No significant difference was detected in terms of cumulative RFS when compared between assisted reproductive technology (ART) cases and those involving natural conception (NC) (P = 0.707). Conclusions Normal BMI, a shorter time to CR, a prolonged three-month treatment, fewer hysteroscopy procedures, and a thicker endometrium may be positive indicators for successful pregnancies, while relapse before pregnancy may have a negative effect on conception. Moreover, a successful pregnancy protects the endometrium while ART does not increase the risk of recurrence.